The nonlinear workbook : chaos, fractals, cellular automata, neural networks, genetic algorithms, gene expression programming, wavelets, fuzzy logic with C++, java and symbolic C++ programs - 327494 Steeb, Willi-Hans; Hardy, Yorick, 1976-; Stoop, Ruedi (River Edge, NJ : World Scientific Publishing Company, 2008)
22